Case Report: Combined Cataract Surgery and Minimally Invasive Glaucoma Surgery Provide an Alternative Treatment Approach for Lowe Syndrome - Wang, Chen; Zhang, Wenzhe; Wang, Leyi; Liu, Wenhui; Guo, Hui (Frontiers in Medicine, 2022)
We describe the case of a 4-month-old boy who presented with bilateral congenital cataract and high intraocular pressure (IOP) in the left eye, followed by mental retardation and delayed motor development. Genetic investigation revealed the boy had a splicing variant (c.940-11G＞A) of the oculocerebrorenal syndrome of Lowe (OCRL) gene. The boy underwent a lensectomy for congenital cataract in his right eye, and lensectomy combined with a 360° suture trabeculotomy to remove the clouded lens and to control IOP of the left eye. During postoperative one-and-a-half-year follow-up, the boy exhibited an improved visual acuity and a well-controlled IOP without the use of topical IOP-lowering medications. Lowe syndrome is a rare multisystemic disorder that is diagnosed through clinical manifestation and genetic testing. The possibility of Lowe syndrome should be considered in patients presenting with typical triad, and genetic analysis should be performed in time to confirm the diagnosis. We recommend combined cataract surgery and minimally invasive glaucoma surgery (MIGS) as a safe, feasible, and efficient method to treat congenital cataract and glaucoma in Lowe syndrome patients.